Look! look! look! at sculpture - Wallace, Nancy Elizabeth (Marshall Cavendish, 2012)
Three mice "borrow" a postcard which is a reproduction of a sculpture, and from it they learn about color, pattern, line, and shape. Includes instructions for making and sending a postcard.